Enhancing the biofuel upgrade performance for Pd nanoparticles via increasing the support hydrophilicity of metal–organic frameworks. (19th June 2017) - Sun, Qi; Chen, Meng; Aguila, Briana; Nguyen, Nicholas; Ma, Shengqian
Abstract : In this work, the influence of the hydrophilic/hydrophobic nature of metal–organic framework (MOF) materials on the catalytic performance of supported Pd nanoparticles for biofuel upgrade was studied. We show that the introduction of hydrophilic groups on a MOF can greatly enhance the performance of the resultant catalyst. Specifically, Pd nanoparticles supported on MIL-101–SO3 Na with superhydrophilicity (Pd/MIL-101–SO3 Na) far outperforms pristine MIL-101 and the benchmark catalyst Pd/C in the hydrodeoxygenation reaction of vanillin, a model component of pyrolysis oil derived from the lignin fraction. This is attributed to a favorable mode of adsorption of the highly water soluble reactants on the more hydrophilic support in the vicinity of the catalytically active Pd nanoparticles, thereby promoting their transformation.